The Adenosinergic System in Diabetic Retinopathy - J. Vindeirinho; A. R. Santiago; C. Cavadas; A. F. Ambrósio; P. F. Santos (Journal of Diabetes Research)
The neurodegenerative and inflammatory environment that is prevalent in the diabetic eye is a key player in the development and progression of diabetic retinopathy. The adenosinergic system is widely regarded as a significant modulator of neurotransmission and the inflammatory response, through the actions of the four types of adenosine receptors (A1R, A2AR, A2BR, and A3R), and thus could be revealed as a potential player in the events unfolding in the early stages of diabetic retinopathy. Herein, we review the studies that explore the impact of diabetic conditions on the retinal adenosinergic system, as well as the role of the said system in ameliorating or exacerbating those conditions. The experimental results described suggest that this system is heavily affected by diabetic conditions and that the modulation of its components could reveal potential therapeutic targets for the treatment of diabetic retinopathy, particularly in the early stages of the disease.